The Potential Applications of Stem Cell Conditioned Medium Secretome in Knee Cartilage Regeneration: A Systematic Review - Aryana, I Gusti Ngurah Wien; Febyan, Febyan; Ustriyana, Nyoman Gede Grenata Nanda (Universitas Airlangga, 2024)
Background: Articular cartilage injuries often result from trauma, genetic predisposition, and degeneration. These injuries lack inherent regeneration mechanisms due to the absence of blood vessels and limited progenitor cell entry. Osteoarthritis is characterized by gradual cartilage deterioration. Mesenchymal stem cells (MSCs), particularly their secretome including exosomes, hold promise as a regenerative therapy. This review explores the application of MSCs and their secretome to address cartilage defects.Methods: This review was conducted based on PRISMA guidelines. Animal model studies focusing on the use of stem cell secretomes for cartilage regeneration were explored. The search, encompassing PubMed, MEDLINE, the Cochrane Library, Scopus, Web of Science, and Science Direct from January 10, 2023, to July 27, 2023, was conducted utilizing Google Chrome as the search engine. Studies with outcomes based on OARSI or ICRS scores, as well as any additional outcomes related to MSC secretome utilization, cartilage regeneration, and proliferation, were included.Results: Our systematic review identified six studies using MSCs in vivo and in vitro. Synovial membrane-derived MSCs significantly enhanced cartilage regeneration by elevating chondrogenic capabilities. Hydrogel-based systems techniques and 3D-printed scaffolds have emerged for innovative delivery. Specific microRNAs, such as miR-92a-3p, have been recognized for enhancing cartilage regeneration. Strategies for the effective targeting of MSC exosomes to the precise cartilage damage site have been explored.Conclusions: The studies demonstrate the potential of MSC-derived secretomes and exosomes for knee cartilage regeneration in animal models. Further research and clinical trials are needed to refine these approaches for practical application.